Potensi Pengembangan Pariwisata Berbasis Budaya di Desa Wana Kabupaten Lampung Timur - Desmala Sari; Ute Lies Siti Khadijah; Wawan Setiawan; Evi Novianti; Aulia Iskandarsyah (Jurnal Abdimas Pariwisata, 2022)
Cultural Tourism: Identification of Community-Based Cultural Tourism Potential In Bandung In this community service that has been carried out in Wana village, the author wants to explore and examine the tourism potential of the Lampung tribe in Wana Village. Assessing the potential of culture as a tourism object is very important to support developers or local governments to plan and implement village development strategies effectively. The purpose of this service is to find out what is the potential for cultural tourism in Wana Village so that it can support developing sustainable tourism. The result of community service that has been carried out is that Wana Village has several cultural potentials that can be used as tourist attractions, such as traditional houses, traditional ceremonies and clothes, traditional arts, as well as various Lampung culinary specialities that can be developed into sustainable tourism objects. This result is hope as a reference in the field of Lampung cultural tourism which is currently not widely known to the general public and a reference for developers and local governments in formulating a strategy development program or cultural-free marketing in Wana Village.